Effect of cytokinins and auxins on micropropagation of banana (Musa AAA) cv. Albeely by shoot tip explants - H. A. Othman, Mohammed; A. Ali, Mohamed; A. Abdellatif1, Igbal (Gezira Journal of Agricultural Science, 2023)
This study was conducted in the plant tissue culture laboratory at the Agricultural Research Corporation (ARC), Wad Medani, Sudan, during the year 2011. The objective was to develop a micropropagation technique for banana, cv. “Albeely”. Two cytokinins i.e. benzylaminopurine (BAP) and isopentenyladenine (2iP) were tested at 0, 2, 4, 6 and 8 mg/l each on micropropagation of the banana cv. Albeely. The results indicated that 4 mg/l was the best concentration for both cytokinins. Two experiments were conducted to determine the best combinations between 4 mg/l of both BAP and 2iP with different concentrations of indole butyric acid (IBA), i.e. 0, 0.2, 0.4, 0.6, 0.8 mg/l on micropropagation of banana. The results indicated that the best shoot morphogenesis was induced on either 4mg/l BAP combined with 0.8 mg/l IBA or 4 mg/l 2iP with 0.6 mg/l IBA.